(untitled) (Journal of Health, Population and Nutrition, 2013)
Phosphorus is an essential substance in our body, and hypophosphataemia (HP) is well-described in rickets, refeeding syndrome, diabetic ketoacidosis (DKA), and in chronic alcohol-abuse. However, to our knowledge, HP among severely-malnourished children has not been studied in detail, and information on prevalence, severity, and treatment is scarce. Currently, there are only a few published case reports of HP. This case series describes three cases of HP that presented to Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b). Our first case required mechanical ventilation for respiratory distress associated with severe hypokalaemia (K 1.1 mmol/L) and moderate hypophosphataemia (P 2.1 mg/dL). The second case presented with severe sepsis which was associated with symptomatic hypocalcaemia (Ca 1.68 mmol/L), hypokalaemia (K 1.82 mmol/L), and severe hypophosphataemia (P 0.9 mg/dL). The third case presented with pneumonia and sepsis which were complicated by hypokalaemia (K 2.05 mmol/L) and severe hypophosphataemia (P 1.1 mg/dL). Marked lethargy and severe hypotonia were associated with HP in all of these cases. Manifestations of HP are diverse and can occur in association with other electrolyte imbalances, especially among malnourished children. Malnutrition, combined with sepsis, is one of the major killers of children younger than 5 years of age, and both malnutrition and sepsis can cause HP. It is concluded that the underlying causes of morbidity, including HP, should be actively sought and treated to reduce the mortality of children aged below five years. DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13419 J HEALTH POPUL NUTR 2012 Dec;30(4):491-494